Отряд - Евтушенко Алексей Анатольевич (Военно-фантастический бестселлер, 2014)
Экземпляры: ф.4 (20150216) / Инвентарный номер: 46623 / Цена: 180.00 / Авт.знак: Е 27 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6